Unpacking Attrition: A Change of Emphasis - Corman, June; Barr, Lynn; Caputo, Tullio (Canadian Journal of Higher Education, 1992)
In this paper, we critique the conceptual, methodological and ideological issues involved in the university attrition debate in both Canada and the United States and discuss the salient policy implications of attrition research for higher education in Canada. We argue that American attrition research tends to result in policy recommendations aimed at those students who have already demonstrated their ability to succeed academically without assistance. A change of emphasis that places the question of attrition in the context of the role of higher education in society, particularly in relation to the issue of equality of opportunity, is suggested.